Momentum of perturbations in elite squash. - Davies, G.; Fuller, A.; Hughes, M. T.; Murray, S.; Hugehs, M.; Names, N. (World Congress of Performance Analysis of Sport VIII, 2008)
It can be concluded that there is shown to be no comparison between the momentum using winner and errors, to the momentum using perturbations. Nevertheless, after conducting a case study on some of the subjects, indications of usage patterns of perturbations within matches started to emerge form the momentum graphs, which identified specific styles of play. Adding the data from different matches was deemed to be counter-productive to the true value of using these graphs and also the sequential nature of the data involved. There is evidence to indicate that momentum using perturbations can further the analysis in squash. This study can also conclude that the physiological characteristics of physical conditioning has an effect upon the amount of perturbations caused. This could be attributed to a player becoming more urgent towards the end of a match and performing more high risk shots, as evident through rally lengths imposed with the momentum graphs using perturbations. Further research into the points of critical momentum shift could be investigated to whether situations of the match, for example refereeing decisions, caused the some critical swings in momentum within matches. This could be analysed qualitatively by interviewing the players and coaches after the match to see whether there where areas of the match where they thought that the momentum shifted and for what reasons. From the results the interviews could be analysed correspondently with the momentum graphs to identify and confirm the critical incidents within the match and what created momentum instabilities. An extension of this research could also involve an alternative method for identifying perturbations. Rather than a trained analyst recognising them by eye it could be possible to use tracking hardware or software to highlight them automatically using kinematic variables.